Armed conflict and forcible displacement individual rights under international law - Katselli Proukaki, Elena (Routledge research in international law, 2018)
Armed Conflict and Forcible Displacement provides a critical legal analysis of the contemporary international framework, permeating forcible displacement in these circumstances and explores the rights that individuals possess with specific focus on the right not to be displaced and, where this fails, the right to return home and to receive property restitution. It will be of interest to those interested in the fields of international law, human rights law, as well as conflict and war studies.